Data-driven approaches to support engine performance characterization - Paaskoski, Mikko (My University, 2019)
ABSTRACT Engine Data Sandbox is a data repository containing sensor data measured from over 1000 different Wärtsilä engines, which have been operating in marine and power plant applications throughout several years. The Engine Data Sandbox comprehends over 10 terabytes of raw sensor data, when data is uncompressed. Considering this huge amount of data, Engine Data Sandbox potentially contains a lot of hidden, valuable information. In this thesis, Engine Data Sandbox content is described and mapped. Furthermore, utilizing contained raw data, four different data-driven approaches were developed in order to support engine performance characterization and reliability engineering analysis. In addition, during the development of these approaches, comprehensive set of different data preparation functionalities were developed in order to preprocess the raw data of Engine Data Sandbox. Thesis author developed the data-driven approaches relying on the R programming language. Developed data-driven methodologies are: • Load distribution analysis. • Automatic shutdown analysis. • Main feature extraction for relevant sensor signals. • Anomaly detection of sensor signals. Obtained results provided the possibility to characterize engines behaviour on field. Furthermore, they allowed to preliminary investigate engines health over the operating lifetime. The potential usages and limitations, for the data of Engine Data Sandbox, were also identified in this thesis.

TIIVISTELMÄ Engine Data Sandbox on tietovarasto, joka sisältää sensoridataa yli 1000:sta eri Wärtsilän valmistamasta moottorista. Tätä sensoridataa on kerätty eri laiva- ja voimalaitossovelluksista usean eri vuoden ajalta. Engine Data Sandbox käsittää yli 10 teratavua dataa, kun data on pakkaamattomassa muodossa. Ottaen huomion tämän suuren datamäärän, Engine Data Sandbox sisältää potentiaalisesti paljon arvokasta, piilotettua tietoa. Tässä diplomityössä esitellään Engine Data Sandboxin sisältö sekä tutkielman aikana neljä kehitettyä datavetoista sovellusta, jotka hyödyntävät Engine Data Sandboxin raakadataa. Näiden datavetoisten sovellusten tarkoituksena on tukea Wärtsilän moottoreiden luotettavuuden analysointia sekä käyttäytymisen karakterisointia. Näiden sovellusten lisäksi tutkimuksen aikana kehitettiin huomattava määrä erilaisia toiminnallisuuksia Engine Data Sandboxin raakadatan preprosessointiin. Tutkielman aikana kehitettiin R-ohjelmointikielen avulla seuraavat neljä datavetoista sovellusta: • Sovellus analysoimaan moottorin kuorman jakautumista. • Sovellus analysoimaan moottorin automaattisten poiskytkentöjen syitä. • Sovellus merkityksellisten sensorisignaalien pääpiirteiden määrittämiseen. • Sovellus sensorisignaalien poikkeavan käytöksen löytämiseksi. Saadut tulokset mahdollistavat käytössä olevien moottoreiden käyttäytymisen karakterisoinnin. Lisäksi tulokset mahdollistavat alustavan moottoreiden kunnon estimoinnin niiden eliniän aikana. Myöskin Engine Data Sandboxin potentiaalinen käyttötarkoitus sekä rajoitteet tunnistettiin tutkielman aikana.
Keywords: Reliability engineering; Internal combustion engines; Big data analysis; Machine learning; Engine health monitoring; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; Master’s Programme in Industrial Digitalisation